Exploring the Relationship Between Individual and Bundle Implementation of High-Performance Work Practices and Performance: Evidence From Spanish Manufacturing Firms - Manresa, Alba; Bikfalvi, Andrea; Simon, Alexandra (International Journal of Industrial Engineering and Management, 2021)
Companies aiming to increase their firm performance implement specific practices known as High Performance Work Systems (HPWS). Uncertainty remains, however, about the structures included in them. The main purpose of this paper is to analysis the difference between implementing specific HPWP separately or as a HPWS, and their effect on performance aspects, using the Spanish subsample of the European Manufacturing Survey. The results show that these firms’ implementation rates are relatively low compared to the European average, despite over 50% of respondents implementing some of the practices studied (individually or as a bundle). Article history: Received (March 16, 2021); Revised (July 9, 2021); Accepted (July 12, 2021); Published online (September 14, 2021)